The French May : Actors and Dynamics of a Global Crisis - Mathieu, Lilian, (Social Sciences E-Books Online, Collection 2026., 2026)
It is now time to stop revering May 68 as a political myth, but to consider it as it was, meaning as a social movement that unexpectedly turned into a tremendous political crisis, bringing French institutions near to collapse. Relying on original data, such as unprecedented archives and personal interviews with former sixty-eighters, the book brings new light on how the revolt was unleashed not only among Paris students but the whole French population, challenged all established hierarchies, shook culture and mores, deeply affected its participants' life course, and contributed to a worldwide context of protest.